Penafsiran tentang Interaksi Sosial dengan Non-Muslim - Raihani Aththahirah; Lona Mardiati; Muhammad Haikal; Maulana Ikhsan (Reflection : Islamic Education Journal, 2025)
Social interaction between Muslims and non-Muslims is an important theme in communal life. The Qur'an provides clear guidance on how Muslims should interact with people of different faiths. Based on the interpretations of scholars such as M. Quraish Shihab, Hamka, Imam al-Razi, Ahmad Mushthafa al-Maraghi, and Dr. Aidh Qarny, social interaction between Muslims and non-Muslims should be based on the principles of mutual respect, kindness, and fairness. Qur'anic verses such as Surah Al-Mumtahanah 8, Surah Al-Hujurat 13, and Surah Al-Ankabut 46 emphasize the importance of maintaining good relations without coercion in belief and avoiding hateful debates, especially against the unjust. Islam teaches that debates conducted in a good and wise manner will strengthen interfaith relationships and bring people closer to the truth. In this context, Islam emphasizes the importance of maintaining good character in all forms of social interaction to foster peace and harmony in society.